2019
DOI: 10.1016/j.neuron.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Induces Activity, Synaptic, and Transcriptional Remodeling of the Lateral Habenula Associated with Deficits in Motivated Behaviors

Abstract: CHAPTER 1: INTRODUCTION Heterogeneity of major depressive disorder Depression, or major depressive disorder, is a mental disorder that dramatically affects a person's health and life. It is characterized by persistent low mood, inability to feel pleasure in previously enjoyable activities, feeling of low-esteem, fatigue, sleep disturbances, appetite changes, pain without a clear cause, and thoughts of suicide. It has become the leading cause of disability worldwide with over 300 million people affected. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 125 publications
(207 reference statements)
5
118
1
1
Order By: Relevance
“…Anhedonia a core symptom of major depression among humans is modeled by inducing a decrease in responsiveness to rewards, as reflected by the reduced consumption of and/or preference for sweetened solutions (Rzepa and McCabe, 2019). In the present study, the data are in line with previous findings showing that a significant decrease in the percentage of sucrose consumption of mice (Cerniauskas et al, 2019). Red wine extract significantly reversed this behavioral change, which suggested the antidepressant-like function.…”
Section: Sucrose Consumptionsupporting
confidence: 91%
“…Anhedonia a core symptom of major depression among humans is modeled by inducing a decrease in responsiveness to rewards, as reflected by the reduced consumption of and/or preference for sweetened solutions (Rzepa and McCabe, 2019). In the present study, the data are in line with previous findings showing that a significant decrease in the percentage of sucrose consumption of mice (Cerniauskas et al, 2019). Red wine extract significantly reversed this behavioral change, which suggested the antidepressant-like function.…”
Section: Sucrose Consumptionsupporting
confidence: 91%
“…Perhaps, stress-sensitive inputs preferentially synapse onto neurons projecting to specific targets, and differential activation leads to changes in their subsequent gene expression. Indeed, a recent paper found that CaMKII-expressing neurons projecting from the entopeduncular nucleus tended to synapse onto LHb neurons projecting to the VTA; whereas, those from the lateral hypothalamus and VTA tended to synapse onto neurons projecting to the DRN 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Cerniauskas, et al 33 characterized the effect of chronic mild stress on LHb neurons projecting to either the VTA/RMTg or the DRN. They observed greater excitability in neurons projecting to the VTA/RMTg in mice with the greatest composite depressionlike behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Exploiting this genetic knowledge may provide an entry point to specifically probe the functional and behavioral relevance of individual LHb neuronal clusters identified in this study. Alternative to a genetic basis, clusters may emerge according to topographical organization, input-specific connectivity or discrete projection targets (Cerniauskas et al, 2019; Lecca et al, 2017; Meye et al, 2016; Shabel et al, 2012; Valentinova et al, 2019). Our analysis indicates that some LHb neuronal clusters are topographically distinct.…”
Section: Discussionmentioning
confidence: 99%